Clinicopathological analysis of 46 cases with CD4+ and/or CD56+ immature haematolymphoid malignancy: reappraisal of blastic plasmacytoid dendritic cell and related neoplasms. Issue 6 (10th October 2017) - Suzuki, Yuka; Kato, Seiichi; Kohno, Kei; Satou, Akira; Eladl, Ahmed E; Asano, Naoko; Kono, Michihiro; Kato, Yuichi; Taniwaki, Masafumi; Akiyama, Masashi; Nakamura, Shigeo
Abstract : Aims: In this study, we aimed to investigate the clinicopathological features of CD4 + and/or CD56 + immature haematolymphoid malignancy (iHLM), including blastic plasmacytoid dendritic cell neoplasm (BPDCN). Methods and results: We analysed the clinicopathological features of 46 patients diagnosed consecutively with CD4 + /CD56 + iHLM. These cases were categorised into three groups based on their immunohistochemical expression of three plasmacytoid dendritic cell (pDC) markers [CD123, CD303 and T cell leukaemia/lymphoma (TCL1)]: cutaneous BPDCN ( n = 35), non‐cutaneous BPDCN ( n = 6) and non‐BPDCN‐type CD56 + neoplasms ( n = 5). Compared to non‐cutaneous BPDCN, cutaneous BPDCN was associated with an older median age at onset (72 years versus 45 years, P < 0.05), and higher positivity for CD4 ( P < 0.05), CD123 ( P < 0.05) and 2–3 pDC markers (89% versus 50%, P = 0.05). Cutaneous BPDCN was divided into terminal deoxynucleotidyl transferase (TdT) + and TdT − subgroups, which did not differ in prognosis, although TdT + cases showed a lower median onset age (66 years versus 79 years, P < 0.05) and higher frequency of extracutaneous lesions ( P < 0.05). Compared to the BPDCN groups, non‐BPDCN‐type CD56 + neoplasm cases showed higher cytoplasmic CD3 positivity ( P < 0.05) and less frequent BCL‐2 expression ( P < 0.05), and lacked cutaneous lesions. However, the survival curves overlapped. Notably, one case involved an unusual composite neoplasm, comprising CD56 + lymphoblastic lymphoma and mature CD56 + cytotoxic T cell lymphoma. Conclusions: Our present data support the recognition of cutaneous BPDCN as a homogenous entity, in contrast to the non‐cutaneous form. Additional research is warranted to characterise non‐BPDCN‐type CD56 + neoplasms.